A study of mill scale derived hematite process for NiZn ferrite as EMI suppressor in terms of magnetic properties - Hari Z.; Alias M.W.H.; Anuar A.; Hamid N.A. (Medwell Journals, 2023)
Mill scale iron waste from the steel industry can be extracted into useful hematite and produced into a NiZn ferrite as an EMI suppressor. The function of an EMI suppressor is to 'choke' the electromagnetic interference produced by almost all electronic equipment, electrical wiring, wireless networks, etc. The most widely used material is NiZn ferrite as it can work at high frequency. Some good characteristics of NiZn ferrite toroid core is low permeability and high loss, namely resistivity, Relative Loss Factor (RLF) impedance and coercivity. To help the environmental waste problems and reducing cost, hence the idea to convert mill scale from the steel industry waste into hematite (Fe2O3) which is the most important element in producing NiZn ferrite. Successful conversion of the mill scale into hematite was proven by X-Ray Diffraction (XRD) analysis by designing and fabricating a magnetic separator. The NiZn ferrites were prepared by solid state reaction technique. The 3 samples of different methods of hematite extraction were prepared. The ferrites were tested by XRD, Scanning Electron Microscopy (SEM), permeability, RLF and coercivity. The process of hematite conversion by running the HM sample through the magnetic separator followed by permanent magnet shows the best result. It was proven by the sample HM that has the best characteristics for an EMI suppressor such as low permeability (63.6), high RLF (1.23) and high coercivity (5.873 Oe). Medwell Journals, 2017.